Identification of design criteria for chiller plant distribution network in Alabang Town Center, Philippines - Augusto, Gerardo L. (Animo Repository, 2015)
The applicability and limitations of the method in identifying the design criteria for chiller plant distribution network in Alabang Town Center (ATC), A shopping mall in Manila, Philippines in were investigated. The hydraulic calculation technique, chilled-water system simulation and optimization methods developed from previous studies were applied to validate the theoretical results from actual pipe dimensions of the combined Chiller Plant No.1 and Chiller Plant No.2 of ATC. The piping network has constant-volume primary and variable-flow secondary pumping arrangement with temperature difference set-point of 5.56°C. Optimization results for piping network design criteria revealed that minimum overall cost occurred when the velocity limit at primary line was 1.85 m/s and the velocity limits at secondary line and plot take-off both at 3.00 m/s considering a pressure drop limit of 100 Pa/m. Hydraulic calculation results also indicate that it has good agreement with the current piping dimensions of primary and secondary lines of chiller plants main entry points in the Existing wing, Cinema area and Entertainment area. © 2015 The Authors. Published by Elsevier Ltd.